Engagement level analysis in the programming of haptic devices through a brain computer interface (2022)
This paper proposes the use of a brain-computer interface, which allows measuring the neurosignals of the level of commitment in the performance of the telemarketer when performing the task. The methodology to determine the level of haptic assists consists of 4 steps: first, a teleoperation application is selected, which consisted of remotely moving a robot along a predefined path. In steps two and three, the proposed task is executed with and without haptic assistance. In step 4, the robot's paths are analyzed to determine the areas where the operator required a higher or lower level of assistance. The results show that the user takes a significantly longer time to complete the proposed paths, when the haptic assists are not active. It is concluded that the brain-computer interfaces allow detecting the areas where these aids are more necessary and the areas where they can be reduced.